2000
DOI: 10.1016/s0006-3495(00)76820-2
|View full text |Cite
|
Sign up to set email alerts
|

On the Temperature and Pressure Dependence of a Range of Properties of a Type of Water Model Commonly Used in High-Temperature Protein Unfolding Simulations

Abstract: Molecular dynamics simulations of protein folding and unfolding are often carried out at temperatures (400-600 K) that are much higher than physiological or room temperature to speed up the (un)folding process. Use of such high temperatures changes both the protein and solvent properties considerably, compared to physiological or room temperature. Water models designed for use in conjunction with biomolecules, such as the simple point charge (SPC) model, have generally been calibrated at room temperature and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 37 publications
4
32
0
Order By: Relevance
“…These trends are consistent with our earlier work 19 and findings from other groups. 21,22 Further details regarding the behavior of our water model and detailed solvation properties of peptides and proteins have been presented by Beck et al 23 Overall our pure water simulations are in agreement with the available experimental results across a variety of temperatures, suggesting that this water model does not introduce artifacts when used in hightemperature protein denaturation studies.…”
Section: Resultssupporting
confidence: 78%
“…These trends are consistent with our earlier work 19 and findings from other groups. 21,22 Further details regarding the behavior of our water model and detailed solvation properties of peptides and proteins have been presented by Beck et al 23 Overall our pure water simulations are in agreement with the available experimental results across a variety of temperatures, suggesting that this water model does not introduce artifacts when used in hightemperature protein denaturation studies.…”
Section: Resultssupporting
confidence: 78%
“…The force field parameters are normally fit at RT, and it is not surprising that the resulting potential function cannot reproduce some properties at higher temperatures well. The SPC water model may also contribute to the errors in our simulation because, as pointed out recently by van Gusteren and coworkers, the properties of SPC water, such as the thermal expansion coefficient, heat capacity, and diffusion constants deviate significantly from experiments at higher temperatures (24). The same is probably true for the TIP3P water as used in Garcia and Sanbonmatsu's simulation.…”
Section: Resultsmentioning
confidence: 72%
“…2000; Tarek & Tobias 2000Teeter et al 2001;Caliskan et al 2002;Paciaroni et al 2002). Highly viscous solvents, such as trehalose, suppress dynamical transition behaviour (Hagen et al 1995;Cordone et al 1999;Walser et al 2000), and neutron-scattering experiments on enzymes in a range of cryosolvents showed that the dynamical transition behaviour of the protein solution resembles that of the pure solvent (Bizzarri et al 2000;Reat et al 2000;Daniel et al 2003).…”
Section: Solvent Role In the Protein-glass Transitionmentioning
confidence: 99%